Geometric morphometry of pupae to identify four medically important flies (Order: Diptera) in Thailand (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Chaiphongpachara T, Tubsamut P. 2019. Geometric morphometry of pupae to identify four medically important flies (Order: Diptera) in Thailand. Biodiversitas 20: 1504-1509. In this study, we evaluated an outline-based geometric morphometric (GM) approach for species identification from pupae of four common flies medically important in Thailand, Chrysomya megacephala, Lucilia cuprina, Musca domestica, and Boettcherisca nathani. For size estimation, mean perimeter length was used. For shape analysis, Elliptic Fourier Analysis was performed to produce the contour shape variables, which was calculated as Normalised Elliptic Fourier coefficients. Then, principal component analysis was performed on the Normalized Fourier coefficients for discriminant analysis, and used to estimate pupal shape variation among the species. The difference in size and shape between the fly species was analyzed using a non-parametric test based on 1000 permutations after Bonferroni correction for the significance level (p < 0.05). In the size analysis, the mean perimeter length for pupae of B. nathani was the largest (20.35 mm) followed by C. megacephala (14.73 mm), while that for M. domestica was the smallest (11.82 mm). The size differences were statistically significant between all species (p < 0.05). The contour shapes of all pupae were significantly different among all species. The results of this study can be used as a basis for the future application of GM to identify other types of flies via their pupae.
Keywords: Chrysomya megacephala, Geometric morphometric analysis, Lucilia cuprina, Musca domestica, Boettcherisca nathani